Springer Proceedings in Materials: Intelligent Manufacturing and Mechatronics - Radhiyah, Abd Aziz (Springer, 2024)
The fourth edition forum of the Innovative Manufacturing, Mechatronics and Mate-rials Forum 2023 (iM3F 2023) organized by Universiti Malaysia Pahang Al-Sultan Abdullah through its Faculty of Manufacturing and Mechatronic Engineering Tech-nology was held on 7 and 8 August 2023. The main field focuses on Manufacturing, Mechatronics as well as Materials.